2008
DOI: 10.1371/journal.pcbi.1000229
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Sequence Analysis Reveals a Novel Role for ß2* Nicotinic Receptors in Exploration

Abstract: Nicotinic acetylcholine receptors (nAChRs) are widely expressed throughout the central nervous system and modulate neuronal function in most mammalian brain structures. The contribution of defined nAChR subunits to a specific behavior is thus difficult to assess. Mice deleted for ß2-containing nAChRs (ß2−/−) have been shown to be hyperactive in an open-field paradigm, without determining the origin of this hyperactivity. We here develop a quantitative description of mouse behavior in the open field based upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 31 publications
6
36
0
3
Order By: Relevance
“…In M1 of β2 −/− mice, we observe a significant reduction in the dendritic field area, branching complexity, and total number of spines. These mice have higher locomotor activity, spend more time in fast navigatory movements, and spend less time in exploration of their environment (16,35). No significant morphological changes were observed in the associative M2 field, however.…”
Section: Consequences Of the Deletion Of Nachr β2-subunit On Dendriticmentioning
confidence: 98%
See 1 more Smart Citation
“…In M1 of β2 −/− mice, we observe a significant reduction in the dendritic field area, branching complexity, and total number of spines. These mice have higher locomotor activity, spend more time in fast navigatory movements, and spend less time in exploration of their environment (16,35). No significant morphological changes were observed in the associative M2 field, however.…”
Section: Consequences Of the Deletion Of Nachr β2-subunit On Dendriticmentioning
confidence: 98%
“…These frontal cognitive cortical fields are involved in the temporal organization of behavior, behavioral flex ibility, and social behavior in mice (16) and in access to consciousness in humans (38). These cognitive functions are significantly reduced in the β2 −/− mice (16,35,44). We hypothesize that the reduced density of dendritic spines in this cortical field may constitute a critical neurobiological component of these behavioral alterations.…”
Section: Consequences Of the Deletion Of Nachr β2-subunit On Dendriticmentioning
confidence: 99%
“…Studies in knockout mice (β2 −/− ) demonstrated an important role of the receptor containing the β2 subunit in cognitive and executive behaviors (Picciotto et al 1995;Granon et al 2003;Maubourguet et al 2009;Avale et al 2011;Bourgeois et al 2011), neuronal plasticity and development (Ballesteros-Yáñez et al 2010), and nicotine addiction (Picciotto et al 1998;Maskos et al 2005;David et al 2006). Knocking out a particular receptor or protein can mask its role in normal conditions because of the compensation and adaptive mechanisms that can emerge in these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, α7β2nAChR −/− mice showed enhanced motor performance on the rotarod [32] and β2nAChR −/− mice were described as hyperreactive to novelty, suggesting that endogenous nAChR stimulation may exert a tonic control on monoamine-mediated locomotor responses [8]. Hyperactivity associated to β2nAChR deficiency appeared to be linked to selective dissociation of the high-order spatiotemporal organization of locomotor behavior (involving conflict resolution/social interaction) from low-level (more automatic motor behaviors) [9] and to the absence of specific inactive states (corresponding to decision moments) allowing to scan the environment and organize sequences of behavior [10]. Interestingly, hyperactivity of β2nAChR −/− mice can be normalized by selective expression of β2nAChR in the nigrostriatal and mesolimbic brain regions [11].…”
Section: Discussionmentioning
confidence: 99%
“…Central nicotinic cholinergic signaling also regulates energy homeostasis through modulation of energy expenditure and control of spontaneous physical activity [6,7]. In this context, the β2nAChR −/− mice present an elevation in locomotor behavior but a dampened exploration behavior linked to alterations in the dopaminergic system [8][9][10][11]. In addition to these central roles in the brain, more subtle nAChR expression is detected in nonneuronal cell types throughout the body [12][13][14], suggesting a paracrine role for ACh.…”
Section: Introductionmentioning
confidence: 99%